Oficinas terapêuticas no CAPSi: um instrumento de transformação do imaginário social sobre a loucura - D’Paula, Débora Amaral (Universidade Federal do Tocantins, 2024)
This research proposes to think about the therapeutic activities and practices in the Centers for Psychosocial Care for Children and Youth, more specifically, expressive therapeutic workshops, as a potential instrument for transforming the social imaginary about madness. The study was outlined in a historical survey on madness since the Classical Age until the Psychiatric Reform process in Brazil, also paying attention to how the concept of childhood madness was historically constructed, as well as the processes that took place in the provision of mental health care to children and adolescents with mental disorders until the establishment of models of child and adolescent mental health care, the CAPSi. That said, this research hypothesizes that the artistic, cultural, and expressive practices and activities proposed by the substitutive models in mental health, are instruments of subversion to the asylum logic, and once favoring the social reinsertion, autonomy, and singularity of children and adolescents, are allied in the transformation of the imaginary constructed about childhood madness. Therefore, this study, from a bibliographic and documental review, seeks to discuss not only the conceptions of mental health and child and adolescent madness but also the instruments of deinstitutionalization and transformation of the crystallized and historically constructed idea about children and adolescents with mental disorders.